Youth unemployment amidst aged care workers shortages in Australia: Why care about the millennials? - Dhakal, Subas P.; Sutcliffe, J. (Emerald Group Publishing, 2018)
Purpose: The broader challenges of youth employment and ageing population have collectively received global attention in the Sustainable Development Goals. Under the assumption that there are fertile opportunities to judiciously address the youth unemployment and labour shortages within the aged care sector, the purpose of this paper is to draw on the experiences of millennial aged care workers (MACWs) in Western Australia (WA). Design/methodology/approach: The paper makes use of an exploratory research approach which involved three aged care facilities in WA. A total of 19 semi-structured interviews with MACWs (n=14), human resources managers of aged care facilities (n=3), government official (n=1), and a union representative (n=1) were carried out. Findings: The results revealed that millennials prefer positive working relationships with managers, co-workers and residents, flexible work schedules and value the altruistic nature of the profession. In addition, unsupportive work environment and workplace pressure to satisfy the needs of elderly residents reduced millennials’ desire to remain in the industry. Originality/value: These findings have the potential to inform human resources managers, aged care service providers and policy makers to formulate strategies to retain the millennials, especially the unemployed, considered vital to the vitality of the Australian aged care industry.